2016
DOI: 10.1111/coa.12560
|View full text |Cite
|
Sign up to set email alerts
|

A review of simulation platforms in surgery of the temporal bone

Abstract: At present, cadaveric simulation remains the best platform for training in temporal bone surgery. Technological advances enabling improved materials or modelling mean that in the future plastic or virtual platforms may become comparable to cadaveric platforms, and also offer additional functionality including patient-specific simulation from CT data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 48 publications
0
41
0
11
Order By: Relevance
“…Both open and minimally invasive procedures were taught on cadavers, in more than eight different surgical specialties including trauma, general surgery, neurosurgery and GI surgery [7][8][9][10][11]. Basic (e.g.…”
Section: Participants and Interventionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both open and minimally invasive procedures were taught on cadavers, in more than eight different surgical specialties including trauma, general surgery, neurosurgery and GI surgery [7][8][9][10][11]. Basic (e.g.…”
Section: Participants and Interventionmentioning
confidence: 99%
“…Nevertheless, if the systematic review is assessing simulation for a specific procedure that cannot be adequately replicated with other forms of simulation (e.g. temporal bone surgery), the authors are found to be more enthusiastic about cadaveric simulation [8,9].…”
Section: Participants and Interventionmentioning
confidence: 99%
See 3 more Smart Citations